2022
DOI: 10.1088/1748-9326/ac4ec2
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the regional stranded asset risks from new coal plants under 1.5 °C

Abstract: Momentum to phase out unabated coal use is growing globally. This transition is critical to meeting the Paris climate goals but can potentially lead to large amounts of stranded assets, especially in regions with newer and growing coal fleets. Here we combine plant-level data with a global integrated assessment model to quantify changes in global stranded asset risks from coal-fired power plants across regions and over time. With new plant proposals, cancellations, and retirements over the past five years, glo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…In addition, their sector-specific results cannot be easily translated into economy-wide stranding estimates (see Cahen-Fourot et al, 2021, for a discussion of stranding network effects). However, our results appear to be roughly in line with the results from Johnson et al (2015) and on the lower end of the results from Edwards et al (2022). 35 In addition to physical capital, reserves of fossil fuels could also be left stranded in lowcarbon scenarios.…”
Section: Stranded Assetssupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, their sector-specific results cannot be easily translated into economy-wide stranding estimates (see Cahen-Fourot et al, 2021, for a discussion of stranding network effects). However, our results appear to be roughly in line with the results from Johnson et al (2015) and on the lower end of the results from Edwards et al (2022). 35 In addition to physical capital, reserves of fossil fuels could also be left stranded in lowcarbon scenarios.…”
Section: Stranded Assetssupporting
confidence: 85%
“…Johnson et al (2015), using the MESSAGE-MACRO model, find optimal stranding of coal plants in a 2 • C scenario to be between $200 billion and $600 billion, depending on how rapidly policies are implemented Edwards et al (2022),. using the GCAM model, find stranded physical capital in the coal sector in the range of $1-1.4 trillion.…”
mentioning
confidence: 99%
“…Overall, metrics that place a high impact value on CH 4 early on require an accelerated phaseout of coal and natural gas, whereas those with a high value later on place limits on sustained use of fossil fuels with CCS at current CH 4 intensities of fossil fuel infrastructure. For metrics that increase the impact value assigned to CH 4 over time, deploying new CH 4 -intensive technologies (e.g., CCS) may not be economical, as these assets may be stranded ahead of their design lifetime to meet emissions targets (Edwards et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that many rapidly developing countries, where the majority of coal capacity has been added in the last two decades (Tong et al, 2019), would need to prematurely retire their coal fleet, that is, close their coal power plants before its usual operating lifetime of 40-60 years is complete. This places the burden of stranded assets disproportionately on those rapidly developing regions (Edwards et al, 2022). Overall, coal phaseout raises concerns related to equity in international climate politics (Jakob et al, 2020) and also to "societal feasibility" (Spencer et al, 2018), given that fast rates of coal decline have rarely been observed historically (Vinichenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%